Development of Mathematics Learning Tools in the Context of Riau Malay Culture to Improve Students Mathematical Problem Solving Ability - Rianti, Resmi; Saragih, Sehatta; Zulkarnain, Zulkarnain (FKIP-Universitas Riau, 2020)
This research was motivated by the lack of learning devices that are considered to be able to train students mathematical problem solving abilities. The purpose of this study was to develop mathematical learning tools that meet the valid, practical, and effective requirements to improve the mathematical problem solving abilities of students in grade VIII SMP on flat side space. The development model used was the 4D model. Based on the results of the validation data analysis, it was concluded that the learning device developed was valid. The results of the syllabus validation were 80.56%, RPP 81.43%, LKPD 87.34%, pretest questions 78.94%, posttest questions 79.86%. This learning tool fulfills the practical requirements in large group trials with an average performance result of 93.06% and an average questionnaire response of students 91.21%. The use of effective learning tools has improved the student learning outcomes. Development of learning tools can significantly improve students mathematical problem solving abilities at a significant level of 0,000 with α =0.05. This shows that the learning tools that was developedalready meet the valid, practical, and effective requirements and can improve students' mathematical problem solving abilities.